Conhecimento sobre atividade física dos estudantes de ensino médio da zona urbana da cidade de Pelotas - Silveira, Eder da Fontoura (2010)
This study evaluated the knowledge about physical activity and its relation to the prevention of chronic disease and physiological effect on the human body in adolescents who attend classes in high school in the urban area of Pelotas. It was conducted a cross-sectional, school-based approach with 1233 individuals aged 13 to 19 years. The questionnaire originated a score (range 0-22 points). Mean score for the sample was 14.1 (SD = 3.0). More than 60% of adolescents correctly associated physical activity to prevent chronic diseases like high blood pressure, high cholesterol, osteoporosis and depression. Higher level of knowledge was positively associated to higher social strata, white color and higher age and grade. Among women, those who had a self-perceived health between good and excellent also had the highest knowledge. Education programs for health must be desenvolved to infor young people about the influence of the risk behavior in an attempt to minimize the sendentary behavior and possibly the number of obese in adolescence and adulthood.